Slope Stability Analysis for Proposed Footing Construction Seated on Sloppy Ground - Deepika, Tirumala; ., . (International Journal of Engineering and Technology, 2018)
Slope failures are one of the common phenomena in the Geotechnical failures. Thus it is needed to arrest the failure through proper mechanism.  Considering this as a scope the present study is oriented to address the analysis of sloppy site where the proposed building foundation to be constructed with different slopes as a natural construction site. The stability is checked and the anchors are used to improve the stability aspect of slope. The study found that the homogeneous soil slope is improved its safety under the usage of anchors.